Managing engineering and technology an introduction to management for engineers - Babcock, Daniel L.; Morse, Lucy C. (Prentice-Hall international series in industrial and systems engineering, 2014)
or courses in Technology Management, Engineering Management, or Introduction to Engineering Technology. Managing Engineering and Technology is designed to teach engineers, scientists, and other technologists the basic management skills they will need to be effective throughout their careers